„Grenzkontakte“. Seit mehr als 25 Jahren gelebte deutsch-niederländische Kooperation zwischen älteren Studierenden aus Oldenburg und Groningen/Drenthe - Brokmann-Nooren, Christiane (Zeitschrift Hochschule und Weiterbildung, 2015)
Keywords: Drente; Grenzüberschreitende Kooperation; Hochschule; OA/Volltext; Oldenburg (Oldenburg); Provinz Groningen; Student

Die Geschichte, wie sie in Holland geschrieben worden war... Die ungarische Rezeption der niederländischen Geschichtsideen im 17. Jahrhundert - Csorba, Dávid (Acta Neerlandica, 2015)
The ideas on history in Protestant Holland in 17-century had much more impact on ideology of Hungarian Peregrinants, than it was considered to be before, not only in ecclesiastical, but in secural area of research history also. It had to be emphasied that there was a turn at the beginning of the 17th century: beside the Barokk, the dominant art and cultural historcal viewpoint came up a general spiritual reform that had several label, and lived without determining its confession. There were in protestant (e.g. Nadere reformatie, Puritanism, Pietism, Herrnhutianism, Methodism) and in catholical denominations (e.g. Jansenism), but also in Jewish religion (e.g. hasidical misticism). In parallel with that phenomenon had changed theories on history. The Hungarian undergraduates had from 1622 in Franeker and in the other Universities in Holland studied, and perceived the alteration of world view. In that paper my scope was investigating the circumstances of that changing, and demonstrating the difficulty of the research.
Keywords: Geschichtsbild; Kulturaustausch; OA/Volltext; Student; Ungarn